2022
DOI: 10.3389/fcell.2022.809425
|View full text |Cite
|
Sign up to set email alerts
|

Gα12 and Gα13: Versatility in Physiology and Pathology

Abstract: G protein-coupled receptors (GPCRs), as the largest family of receptors in the human body, are involved in the pathological mechanisms of many diseases. Heterotrimeric G proteins represent the main molecular switch and receive cell surface signals from activated GPCRs. Growing evidence suggests that Gα12 subfamily (Gα12/13)-mediated signaling plays a crucial role in cellular function and various pathological processes. The current research on the physiological and pathological function of Gα12/13 is constantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 205 publications
(274 reference statements)
0
3
0
Order By: Relevance
“…This leads to the activation of a host of downstream transcription factors, notably NF-κB, a major player in the expression of genes encoding inflammatory factors ( 33 ). In the case of Gα12/13, activation leads to Rho-mediated cytoskeleton reorganization, collaborating with Gβγ to regulate immune cell chemotaxis to inflammation sites - these actions primarily result in pro-inflammatory effects ( 34 , 35 ). Gαq coupled with GPR35 directly inhibits the PI3K catalytic subunit and then suppresses Akt activation.…”
Section: Gpr35 Involved Inflammation-related Pathwaysmentioning
confidence: 99%
“…This leads to the activation of a host of downstream transcription factors, notably NF-κB, a major player in the expression of genes encoding inflammatory factors ( 33 ). In the case of Gα12/13, activation leads to Rho-mediated cytoskeleton reorganization, collaborating with Gβγ to regulate immune cell chemotaxis to inflammation sites - these actions primarily result in pro-inflammatory effects ( 34 , 35 ). Gαq coupled with GPR35 directly inhibits the PI3K catalytic subunit and then suppresses Akt activation.…”
Section: Gpr35 Involved Inflammation-related Pathwaysmentioning
confidence: 99%
“…P2RY10 has been demonstrated to activate GNA12/13 signaling, which is crucial for the proliferation of tumor cells [18,17]. To further investigate the downstream pathways of P2RY10, LoVo cells overexpressing GNA13 were generated.…”
Section: The Role Of Gna13 In the Expression Of P2ry10 And Gna13 In L...mentioning
confidence: 99%
“…In addition, high P2RY10 expression can upregulate the expression of GNA12 and GNA13, which are essential for tumor cell proliferation [17]. It has been reported that GNA12/13 activation can accelerate proliferation and tumor formation in small-cell lung carcinoma, ovarian cancer, and hepatocellular carcinoma cells [18]. Therefore, the current study first determined the levels of P2RY10 and lncRNA TRG-AS1 in normal and CRC cell lines, and then explored the functions of TRG-AS1 and P2RY10 in CRC development in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%